Microbiology of drinking water production and distribution - Bitton, Gabriel (2014)
"This book is proposed because it offers a comprehensive coverage of most of the topics pertaining to drinking water microbiology. It concerns the public health aspects of drinking water treatment and distribution and describes the different water treatment processes (pretreatment, coagulation, flocculation,sedimentation, filtration, disinfection) and their impact on waterborne microbial pathogens and parasites. The quality of the treated water may however be degraded in the water distribution system (WDS). Microorganisms attach to surfaces, namely water distribution pipes, and form biofilms which allow their survival and growth, gene exchange and resistance to disinfection. The biofilm environment also allows the survival and potential growth of primary and opportunistic pathogens. The water distribution system may also harbor various organisms (e.g., algae, cyanobacteria, fungi, actinomycetes, free living amoebas, invertebrates, iron and manganese bacteria, nitrifying bacteria) which alter the quality of treated water. The biostability of the treated water is an important factor to consider if one wants to reduce bacterial growth in WDS. Various approaches/methodologies have been proposed to assess the bacterial growth potential in WDS. Due to bioterrorism threats to drinking water safety, one needs to know about the scope of this threat, the microbial agents involved and the safeguards that are put in place to protect this precious resource. The proposed book would not be complete if one fails to discuss the research on drinking water quality in developing countries which experience more the two million deaths resulting from diarrheal diseases. Various simple and low-cost treatment technologies are available for improving the quality of drinking water in developing countries. Finally, due a surge in bottled water sales around the world, there is a great need to know about the microbiological water quality of this resource which is often misunderstood by the public at large"--Provided by publisher.
Keywords: Drinking Water -- microbiology; Water Supply; Developing Countries